Trade Policy and Loss Aversion - Freund, Caroline; Özden, Çağlar (American Economic Review, 2008)
We develop a political economy model where loss aversion and reference dependence are important in shaping people's preferences over trade policy. The policy implications of the augmented model differ in three ways: there is a region of compensating protection, where a decline in the world price leads to an offsetting increase in protection, such that a constant domestic price is maintained; protection following a single negative price shock will be persistent; and irrespective of the extent of lobbying, there will be a deviation from free trade that favors loss-making industries. The augmented model explains protections of the US steel industry since 1980. (JEL F13, F14, L61)